What do unit root tests tell us about unemployment hysteresis in transition economies? - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose This study aims to examine the hysteresis hypothesis in unemployment using monthly data from 13 countries in transition. Design/methodology/approach Stationarity in the unemployment rate of selected transition economies was analyzed using four different group unit root tests, namely, linear, structural breaks, non-linear and structural breaks and non-linear. Findings The empirical results show that the unemployment hysteresis hypothesis is valid for the majority of transition economies, including Bulgaria, Croatia, the Czech Republic, Estonia, Hungary, the Kyrgyz Republic, Latvia, Lithuania, Poland, Romania and Slovenia. However, the results strongly reject the null hypothesis of unemployment hysteresis for the Kazakhstan and the Slovak Republics. Originality/value This study revealed that, for countries in transition, advanced unit root tests exhibit greater validity when compared to standard tests
Keywords: Unemployment hysteresis; Transition economies; Fourier unit root test; Non-linear unit root test